Briquetas para la obtención de biomasa energética a partir de los residuos de maíz (Zea mays) en la comunidad San Miguel de Tres Charcos - Briones Loor, Dayana Jamileth (2019)
The purpose of the research was to prepare briquettes for obtaining energy biomass from corn crop residues, specifically stem and tusa, from the San Miguel de Tres Charcos-Rocafuerte community. The investigation was of an experimental type, the same one that was carried out under the guidelines of the Completely Random Design (DCA) with three treatments that were constituted by three replicas each, against domestic coal as a witness. In total twelve experimental units were studied, the composition of each treatment was 30% binder as a fixed variable and 30% agricultural corn residues of which the composition was: T1 = 60% tusa - 40% stem, T2 = 40% tusa - 60% stem, T3 = 50% tusa - 50% stem. The variables to be measured were: calorific value, resistance to crushing, ash, ignition time and humidity, values that were compared with the Colombian standard NTC 2060. The treatment that on average presented less potential in the generation of calorific value was T1 with 15.14 Mj / kg, in relation to T3 with an average of 15.55 Mj / kg, this being the treatment that complied with the parameters of the NTC 2060 standard regarding the variables of calorific power and ash, resulting in the affirmation of the hypothesis.